1991
DOI: 10.1007/bf01418518
|View full text |Cite
|
Sign up to set email alerts
|

The effects of indomethacin on intracranial pressure, cerebral blood flow and cerebral metabolism in patients with severe head injury and intracranial hypertension

Abstract: In five head-injured patients with cerebral contusion and oedema in whom it was not possible to control intracranial pressure (ICP) (ICP greater than 20 mmHg) by artificial hyperventilation (PaCO2 level 3.5-4.0 kPa) and barbiturate sedation, indomethacin was used as a vasoconstrictor drug. In all patients, indomethacin (a bolus injection of 30 mg, followed by 30 mg/h for seven hours) reduced ICP below 20 mmHg for several hours. Studies of cerebral circulation and metabolism during indomethacin treatment showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 32 publications
3
74
2
Order By: Relevance
“…Other inhibitors of cyclooxygenase, such as aspirin and ibuprofen, will not result in cerebral vasoconstriction. 22 Alternative mechanisms include interference with the regulation of cerebrovascular tone mediated by extracellular pH, 23 a reduction of cerebral temperature, 24 as well as a direct non-prostaglandin-mediated vasoconstrictive effect. 25 Our study was not designed to dissect this complexity, although we did show evidence of decreased prostanoid formation without effects on body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Other inhibitors of cyclooxygenase, such as aspirin and ibuprofen, will not result in cerebral vasoconstriction. 22 Alternative mechanisms include interference with the regulation of cerebrovascular tone mediated by extracellular pH, 23 a reduction of cerebral temperature, 24 as well as a direct non-prostaglandin-mediated vasoconstrictive effect. 25 Our study was not designed to dissect this complexity, although we did show evidence of decreased prostanoid formation without effects on body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…55 In a patient with spaceoccupying hemispheric infarction, indomethacin was effective in transiently reducing ICP and improving CPP after all other conventional therapies had failed, and repeated boluses continued to be effective. 56 However, a critical decline in cerebral blood flow with secondary ischemia may occur as a result of cerebral vasoconstriction.…”
Section: Bardutzky and Schwabmentioning
confidence: 99%
“…56 However, a critical decline in cerebral blood flow with secondary ischemia may occur as a result of cerebral vasoconstriction. 55 Given the lack of systemic clinical trials, indomethacin for the treatment of postischemic swelling remains experimental.…”
Section: Bardutzky and Schwabmentioning
confidence: 99%
“…The only tomographic study on living animals (Schumann et al, 1996), found no change of the global CMR O 2 but interestingly (see below) a small and significant increase of CMR O 2 in thalamus and pons. In adult humans, the effect of indomethacin on CMR O 2 was assessed only by the arterio-venous difference (Wennmalm et al, 1981;Jensen et al, 1991;Dahl et al, 1996;Bundgaard et al, 1996) and no significant change was observed in any of these studies. However, a study of preterm infants with near-infrared-spectroscopy of cytochrome oxidase indicated reduced oxygenation (Benders et al, 1995).…”
Section: Effect Of Indomethacin On Cmr Omentioning
confidence: 99%
“…We then tested the properties of the extended model equation by calculating the magnitude of the equation parameters, which would accurately predict the values of oxygen consumption measured in the course of drug-induced lowering of CBF. We used indomethacin, which lowers blood flow, probably by nonselectively inhibiting cyclooxygenase-1 (COX-1) and -2 (Jensen et al, 1991(Jensen et al, , 1993Dahl et al, 1996;Imberti et al, 1997;Zonta et al, 2003), although other mechanisms have also been proposed (Wang et al, 1993;Parfenova et al, 1995).…”
Section: Introductionmentioning
confidence: 99%